Rheological comparison between control and Dupuytren fibroblasts when plated in circular micropatterns using atomic force microscopy - Pérez-Domínguez, Sandra; Werkmeister, Elisabeth; Marini, Maria Luisa; Dupres, Vincent; Janel, Sébastien; Lafont, Frank; Radmacher, Manfred (Frontiers in Physics, 2022)
In tissue, cells are obliged to confine and adapt to a specific geometric shape due to the surrounding environment constraints. In healthy conditions, fibroblasts present an elongated shape, however, changes in biochemical and physical properties of the extracellular matrix could distort cell shape, inducing a pathological state. We have studied fibroblasts mechanical behavior under circular geometrical constraints. Circular micropatterns serve us to force fibroblasts to acquire a different shape from that of healthy tissue, inducing a possible pathological condition. Three different fibroblast types from the Dupuytren disorder, all coming from the same patient, were confined in circular-shaped micropatterns of three different diameters (25, 35 and 45 µm) and mechanical properties were evaluated using the Atomic Force Microscope (AFM). We found that control fibroblasts mechanics (apparent Young’s modulus) increase with increasing pattern diameter and comes together with a decrease in cell height and in loss tangent, translated in a more solid-like behavior. We hypothesize that these results resemble to the transition towards myofibroblast phenotype, ameliorating cytoskeleton formation and organization as well as enhancing cell contraction. Scar and Dupuytren fibroblasts did not display major changes in cell mechanics and cell height when changing pattern diameter, suggesting that they are less affected by physical changes in the environment as they can adapt their shape to the geometrical dimensions. Therefore, our findings demonstrate that combining micropatterning and AFM measurements provide a powerful tool to study cell mechanics inducing constraints onto the cell and thus mimicking certain aspects of the tissue environment in both healthy and pathological states.